Antiproliferative and Antioxidant Activities and Mycosporine-Like Amino Acid Profiles of Wild-Harvested and Cultivated Edible Canadian Marine Red Macroalgae - Athukorala, Yasantha (Molecules, 2016)
Antiproliferative and antioxidant activities and mycosporine-like amino acid (MAA) profiles of methanol extracts from edible wild-harvested (Chondrus crispus, Mastocarpus stellatus, Palmaria palmata) and cultivated (C. crispus) marine red macroalgae were studied herein. Palythine, asterina-330, shinorine, palythinol, porphyra-334 and usujirene MAAs were identified in the macroalgal extracts by LC/MS/MS. Extract reducing activity rankings were (p < 0.001): wild P. palmata > cultivated C. crispus = wild M. stellatus > wild low-UV C. crispus > wild high-UV C. crispus; whereas oxygen radical absorbance capacities were (p < 0.001): wild M. stellatus > wild P. palmata > cultivated C. crispus > wild low-UV C. crispus > wild high-UV C. crispus. Extracts were antiproliferative against HeLa and U-937 cells (p < 0.001) from 0.125–4 mg/mL, 24 h. Wild P. palmata and cultivated C. crispus extracts increased (p < 0.001) HeLa caspase-3/7 activities and the proportion of cells arrested at Sub G(1) (apoptotic) compared to wild-harvested C. crispus and M. stellatus extracts. HeLa cells incubated with wild P. palmata and cultivated C. crispus extracts also exhibited morphological changes characteristic of apoptosis (shrinkage, rounding). Thus, extracts rich in low-polarity usujirene and polar palythine and asterina-330 MAAs were antiproliferative as inducers of apoptosis in HeLa cells.